ANALISIS WAKAMONO KOTOBA DALAM CHANNEL YOUTUBE JHONNYS’ JR. VLOG HIHI JETS - Sekar Puji Lestari (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2021)
The aims of this essay is to describe wakamono kotoba on the YouTube channel Jhonnys' Jr. HiHi Jets vlog which is reviewed from the pattern of word formation, words meaning, and the phenomenon of using wakamono kotoba. The data collection method used was the note-taking method and analyzed using the referential equivalent method, then the research results would be described descriptively. The results of this study were 27 wakamono kotoba found on the YouTube channel Jhonnys' Jr. HiHi Jets vlog consists of five words formation that is clipping, affixation, foreign language borrowing, composition, and sound conversion. It was found that wakamono kotoba has changes in meaning and function from its original form, this word means to show a feeling of disbelief or surprise and its function changes to an adverb, and there are words that has changes in meaning without a word formation process, as well as words that do not changes its original meaning and form. Wakamono kotoba is used by young people to convey their feelings and thoughts with exaggeration.